SPC in service industry: case in teaching and learning process variability monitoring - Zolkepley, Z.; Djauhari, M. A.; Salleh, R. M. (2018)
Statistical Process Control (SPC) technique have long been developed and implemented for quality improvements in manufacturing process. However, it is not so developed in service industry and particularly in teaching and learning process. On the other hand, it is easier to monitor manufacturing industrial process than monitoring teaching and learning process. In the former, the sub-group size is small and constant while in the latter, it is large and nonconstant. In this paper we focus on analyzing the disparity of teaching and learning process variability among classes in a Sekolah Menengah Kebangsaan using the improved generalized variance chart. For that purpose, the appropriate control limits will be developed such that it can be used for general sampling design. The result will be used to monitor the variability of teaching and learning process. A diagnostic tool will also be delivered to understand why, if any, a class is out-of-control.